Pharmacological Mechanisms and Clinical Application Research Progress of Erdong Decoction in Diabetes Mellitus - Lin, Chanchun; Wang, Juanjuan; Xiao, Xiaojun; Zhang, Nan (Journal of Contemporary Medical Practice, 2026)
To summarize the material basis, pharmacological mechanisms and clinical application status of Erdong Decoction for diabetes mellitus, so as to provide references for its basic research and clinical syndrome differentiation medication. Relevant domestic and foreign literatures published in recent years were retrieved. The research progress of Erdong Decoction intervening diabetes mellitus was systematically reviewed from the perspectives of formula compatibility, bioactive components, pharmacological effects and clinical applications. Erdong Decoction contains various bioactive components including flavonoids, saponins and alkaloids. It exerts hypoglycemic effects through multiple pathways such as improving insulin resistance, regulating glucose and lipid metabolism, anti-inflammation and anti-oxidation. Clinically, it can be used alone or combined with western medicines to treat diabetes mellitus and its complications including diabetic nephropathy and diabetic retinopathy. Erdong Decoction achieves definite therapeutic efficacy for diabetes mellitus with yin deficiency and dryness-heat syndrome, and integrated traditional Chinese and western medicine treatment presents prominent advantages. Further experimental verification on the holistic action mechanism of the complete formula is required in subsequent studies.